The contribution of jurisdiction as a technique of demand side regulation in claims for the recovery of cultural objects. (4th May 2015) - Gillies, Lorna E.
Abstract : This article considers the role of jurisdiction in supporting private claims for the cross-border recovery of cultural objects from an EU member state. In particular, this article considers a new, "sui generis" 1 special jurisdiction rule in Article 7(4) of Regulation EU 1215/2012, the Brussels I Recast Regulation. Article 7(4), inter alia, enables "(A) person domiciled in a Member State to be sued in the courts of another Member State […] as regards a civil claim for the recovery, based on ownership, of a cultural object as defined in point 1 of Article 1 of Directive [93/7/EEC] initiated by the person claiming the right to recover such an object, in the courts for the place where the cultural object is situated at the time when the court is seised". This special jurisdiction rule is a welcome development towards facilitating the return of a cultural object from the place where it is seized (for example where there is market demand or when the object is in transit), to a party asserting ownership. In practice the utility of this special jurisdiction rule will depend upon its scope and interpretation by the Court of Justice together with its ability to offer a "counterbalance" 2 to Article 4 and the other special grounds of jurisdiction in the Brussels I Recast Regulation. This paper concludes that this special jurisdiction rule is a key step towards an EU-led "transnational policy of protection of cultural property", 3 which may require further approximation of EU private international law in the future.